2022
DOI: 10.32322/jhsm.1017712
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of idiopathic pulmonary fibrosis and chronic hypersensitivity pneumonia in terms of anterior mediastinal fat properties

Abstract: Aim:The shape and physical properties of the anterior mediastinum can be easily affected by inflammatory lung diseases, tuberculosis, empyema, radiotherapy, chronic fibrotic lung diseases, previous surgery, and after steroid therapy. We planned to compare the properties of anterior mediastinal fat (AMF) in 3 different groups: patients with idiopathic pulmonary fibrosis (IPF), patients with chronic hypersensitivity pneumonia (cHP), and in the healthy control group. We investigate the AMF shape, dimensions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In our study, we found the rate of smoking to be 51.7% higher in our patient group with intertwined comorbidities. Smoking rates in hospitalized patients are generally reported at higher rates in parallel with our findings (12,13). Smoking is among the important risk factors in the etiology of the underlying diseases of our patients.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found the rate of smoking to be 51.7% higher in our patient group with intertwined comorbidities. Smoking rates in hospitalized patients are generally reported at higher rates in parallel with our findings (12,13). Smoking is among the important risk factors in the etiology of the underlying diseases of our patients.…”
Section: Discussionsupporting
confidence: 89%